Clinical significance of antibodies to the phosphatidylserine/prothrombin complex - T. M. Reshetnyak; F. A. Cheldieva; M. V. Cherkasova; A. M. Lila (Современная ревматология, 2022)
Classical serological markers of antiphospholipid syndrome (APS) are antibodies to cardiolipin, antibodies to β2-glycoprotein 1, and lupus anticoagulant. The utility of testing other antiphospholipid antibodies, not included in the classification criteria for improving the diagnosis of autoimmune thrombophilia continues to be debated. The review presents literature data on the study of antibodies to prothrombin and the phosphatidylserine/prothrombin complex in patients with systemic lupus erythematosus and APS.